Implementation of The Scientific Method in Students' Logical Thinking Skills in The 5th Grade Science Material of Islamic Elementary School: Implementasi Metode Saintifk Dalam Keterampilan Berpikir Logis Siswa pada Materi IPA Kelas V Madrasah Ibtidaiyah - Rozhak, Miftakhur; Nurdyansyah (Universitas Muhammadiyah Sidoarjo, 2022)
In this study, the authors raised the issue of how to implement the scientific method in the logical thinking skills of students in the fifth grade science material at MI Ma'arif Kedensari. Based on the results of the interview with the fifth grade teacher, Mi Ma'arif, who said that the learning outcomes of some students in fifth grade were still below the KKM standard which should have been able to reach a score of 75, this was due to the factor of delays in students' thinking and also the less than optimal model. used by the teacher. The purpose of this study was to determine the Implementation of Scientific Methods in Students' Logical Thinking Skills in Science Subject Class V MI Ma'arif Kedensari. To achieve the objectives in this study, the research method used by the researcher is a qualitative descriptive method, in which the research method is based on valid science, and other facts that may become objects of knowledge by using observation, interview, and documentation techniques. to complete the data and information needed by researchers. The results of this study indicate that the use of scientific methods in students' logical thinking skills in learning natural science class V MI Ma'arif Kedensari has increased because when learning takes place students are able to construct knowledge by thinking and reasoning using logic to complete tasks based on knowledge and experience in daily activities and new knowledge given during discussion activities.